ISLAM DAN HAK ASASI MANUSIA DALAM PENDIDIKAN - Ahmad Darmadji (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2012)
This paper analyzes the issue of human rights in the Islamic perspective and its relationship to education in Indonesia. That vision of Islam as mercy for universe can be seen from the universal values and the concern for the basic needs of every person who later becomes a part of human rights. Basic needs are basically in line with the thinking of international human rights which are declared as universal declaration of human rights. Fulfillment and protection of basic needs which are needed to ensure that all people get their rights properly.